Extension of the best approximation operator in Orlicz spaces and weak-type inequalities - Sergio Favier; Felipe Zò (Abstract and Applied Analysis)
We consider an extension of the best approximation operator from an Orlicz space L φ to the space L φ′, where φ′ denotes the derivative of φ, and we prove a weak-type inequality in this space. Further, we obtain some strong inequalities for suitable L ψ spaces.